Sex Differences in Treatments, Relative Survival, and Excess Mortality Following Acute Myocardial Infarction: National Cohort Study Using the SWEDEHEART Registry - Alabas, Oras A; Gale, Chris P; Hall, Marlous; Rutherford, Mark J.; Szummer, Karolina; Lawesson, Sofia Sederholm; Alfredsson, Joakim; Lindahl, Bertil; Jernberg, Tomas (Journal of the American Heart Association, 2017)
Background This study assessed sex differences in treatments, all‐cause mortality, relative survival, and excess mortality following acute myocardial infarction. Methods and Results A population‐based cohort of all hospitals providing acute myocardial infarction care in Sweden (SWEDEHEART [Swedish Web System for Enhancement and Development of Evidence‐Based Care in Heart Disease Evaluated According to Recommended Therapies]) from 2003 to 2013 was included in the analysis. Excess mortality rate ratios (EMRRs), adjusted for clinical characteristics and guideline‐indicated treatments after matching by age, sex, and year to background mortality data, were estimated. Although there were no sex differences in all‐cause mortality adjusted for age, year of hospitalization, and comorbidities for ST‐segment–elevation myocardial infarction (STEMI) and non‐STEMI at 1 year (mortality rate ratio: 1.01 [95% confidence interval (CI), 0.96–1.05] and 0.97 [95% CI, 0.95–0.99], respectively) and 5 years (mortality rate ratio: 1.03 [95% CI, 0.99–1.07] and 0.97 [95% CI, 0.95–0.99], respectively), excess mortality was higher among women compared with men for STEMI and non‐STEMI at 1 year (EMRR: 1.89 [95% CI, 1.66–2.16] and 1.20 [95% CI, 1.16–1.24], respectively) and 5 years (EMRR: 1.60 [95% CI, 1.48–1.72] and 1.26 [95% CI, 1.21–1.32], respectively). After further adjustment for the use of guideline‐indicated treatments, excess mortality among women with non‐STEMI was not significant at 1 year (EMRR: 1.01 [95% CI, 0.97–1.04]) and slightly higher at 5 years (EMRR: 1.07 [95% CI, 1.02–1.12]). For STEMI, adjustment for treatments attenuated the excess mortality for women at 1 year (EMRR: 1.43 [95% CI, 1.26–1.62]) and 5 years (EMRR: 1.31 [95% CI, 1.19–1.43]). Conclusions Women with acute myocardial infarction did not have statistically different all‐cause mortality, but had higher excess mortality compared with men that was attenuated after adjustment for the use of guideline‐indicated treatments. This suggests that improved adherence to guideline recommendations for the treatment of acute myocardial infarction may reduce premature cardiovascular death among women. Clinical Trial Registration URL: https://www.clinicaltrials.gov. Unique identifier: NCT02952417.